IMPROVEMENT OF ESTIMATION METHOD FOR BATTERY CELL HEAT GENERATION - Kulranut, J.; Depaiwa, N.; Yenwichai, T.; Intano, W.; Masomtob, M. (My University, 2021)
This work represents a new experimental method to precisely estimate the heat generation of the battery cell by reducing heat losses to the ambient. The temperature ambient in the chamber is controlled to be close to the battery cell temperature as much as possible in order to reduce the heat loss from the battery to the ambient. The battery is covered by an insulator, and the heat loss due to the heat conduction at the electric connectors is also considered. Therefore, the heat generation term is absorbed by the heat capacity term; in other words, the heat generation of the battery cell can be calculated via the rising temperature of the heat capacity term and the heat loss of the connectors. Consequently, this new method can obtain the precision of the estimated heat generation that can be used to design an appropriate battery thermal management system for the battery pack.
Keywords: Battery cell; Battery thermal management system; Heat generation